Pyrrolo[3,4-c]- and thieno- [3,4-c]isoquinolines — new heterocyclic hits for the drag design of oncolytic compounds - Bogdan, N.M.; Bogza, S.L.; Pendiukh, V.V.; Stepanova, D.S.; Sujkov, S.Yu. (Reports of the National Academy of Sciences of Ukraine, 2020)
The synthesis and cyclization reactions of 3-amino-4-arylpyrroles and 3-amino-4-arylthiophenes with aromatic and heterocyclic aldehydes under the conditions of the Pictet—Spengler reaction are investigated. The course of the reaction of 2-formyl-2-(3,4-dimethoxyphenyl)-acetonitrile with aminomalonic ester was analyzed and the effect of the reaction conditions on the output of intermediate enamine was studied by NMR to inves tigate its E/Z isomerism in solution. A simple method for the preparation of methyl 1H-3-amino-4-(3,4-dimethoxyphenyl)- pyrrole carboxylate was developed. Optimization of the cyclization reaction of 3-amino-4- arylpyrrole with benzaldehydes in the Pictet—Spengler conditions was carried out. The dependence of the output of the cyclization products of aminopyrroles on the substrate — catalyst ratio is shown. The pyrrolo [3,4-c] isoquinoline derivatives were obtained. A preparative method for the synthesis of diethyl 2-[(E, Z)-2-cyano-2- (3,4-dimethoxyphenyl)ethen-1-yl]oxy-propanedioate was developed, and the possibilities of its cyclization to 3-amino-4-(3,4-dimethoxyphenyl)-furan were investigated. The interaction of methyl 3-amino-4-(3,4-dimetho xyphenyl)-2-carboxylate with functionalized benzaldehydes and heterocyclic aldehydes was studied. Thieno[3,4-c]iso quinoline derivatives with functionalized aryl and heterocyclic substituents in the position 5 were synthesized with good yields. When interacting with ninghydrin, the spiroderivative thieno[3,4-c] isoquinoline — 1,3-dihydro-4′ H-spiroinden-2,5′ - thieno[3,4-c]isoquinoline-1,3-dione was obtained. Synthesized compounds and their derivatives can be promising as building blocks for the molecular design of new biologically active substances.